Research progress on the N gene of Akabane virus - Wang, Ruining; Liang, Fang; Lan, Xiaolin; Li, Gan; Li, Feng; Zhao, Mengmeng (Frontiers in Veterinary Science, 2025)
Akabane disease, an arthropod-borne viral infection transmitted by Culicoides mosquitoes, causes severe reproductive disorders in livestock, including abortion, stillbirth, and congenital arthrogryposis-hydranencephaly syndrome. Caused by Akabane virus (AKAV), a single-stranded negative-sense RNA virus of the genus Orthobunyavirus (family Peribunyaviridae), this pathogen poses significant economic threats to global cattle and sheep industries. This review comprehensively examines the nucleocapsid protein (N) encoded by the AKAV S segment, which forms a conserved ribonucleoprotein (RNP) complex essential for viral genome protection, replication, and transcription. The structural characteristics of the N gene were analyzed, its minimal genetic variation across genotypes (97–100% homology), and functional roles in viral pathogenesis. Furthermore, applications of the N gene in diagnostic development (e.g., ELISA, PCR, colloidal gold immunoassays) and vaccine design were summarized, highlighting its utility as an immunogenic target due to high conservation and early antibody in-duction. By integrating these genetic, structural, and applied research advances, this review provides a theoretical foundation for novel control strategies against AKAV.